Effect of Suspension Length and Substrate Curvature on Electric Field Distribution in Emergency Anti-Galloping Cables - Zhongbin Lv; Bo Zhang; Guanghui Liu; Zehui Liu; Chencheng Wang; Lee Li (IEEE Access, 2025)
Galloping of transmission lines caused by wind and ice accumulation poses significant threats to the stability of power grids. While most existing research has focused on preventive anti-galloping devices intended to inhibit galloping before it occurs, emergency mitigation strategies that act after galloping has already developed remain significantly underexplored. This study investigates a 500 kV quad-bundle conductor system and proposes the use of an emergency anti-galloping cable as a mitigation measure. A three-dimensional finite element model is developed to analyze the influence of suspension length and substrate curvature on electric field distribution around key components. Simulation results demonstrate that increasing the suspension length beyond 1.0 m effectively reduces the maximum electric field strength to below the corona threshold of 20 kV/cm. Furthermore, increasing the substrate edge curvature radius to 2.5 mm decreases the maximum surface electric field strength by up to 46.8%. Moreover, the proposed methodology is generalizable to other transmission voltage levels and conductor configurations with appropriate parameter adjustments. This work provides theoretical guidance for the emergency suppression of conductor galloping and contributes to enhancing the reliability of high-voltage transmission systems.